An Update on Idiopathic Intracranial Hypertension - Thurtell, Matthew J. (2010)
Idiopathic intracranial hypertension (IIH) is a condition of unknown etiology often encountered in neurologic practice. It produces non-localizing symptoms and signs of raised intracranial pressure and, when left untreated, can result in severe irreversible visual loss. It most commonly occurs in obese women of childbearing age, but it can also occur in children, men, non-obese adults, and older adults. While it is frequently associated with obesity, it can be associated with other conditions, such as obstructive sleep apnea and transverse cerebral venous sinus stenoses. Recent identification of subgroups at high risk for irreversible visual loss, including black patients, men, and patients with fulminant forms of IIH, help guide the optimal management and follow-up. Ongoing studies of venous anatomy and physiology in IIH patients, as well as a recently begun randomized clinical treatment trial, should provide more insights into this common yet poorly understood syndrome of isolated intracranial hypertension.